1997
DOI: 10.1080/02772249709358460
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of crystal violet over semiconductor zinc oxide powder suspended in aqueous solution

Abstract: The photocatalytic degradation of crystal violet over zinc oxide suspended in aqueous solution has been carried out. The photocatalytic reaction has been studied spectrophotometrically by observing absorbance at different time intervals. The effect of variation of various parameters such as concentration of crystal violet, pH, amount and nature of semiconductor and light intensity on the rate of reaction was observed. A tentative mechanism for this reaction has been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In particular, the organic impurities in contact with photocatalyst surface could act as radical scavengers, influencing the charge recombination process [57,58] and hence worsening the photocatalytic activity of ZnOac500 with respect to ZnOsas500 photocatalyst. It is worthwhile to note that the photocatalytic performances achieved with ZnOsas500 photocatalyst were better than those reported in some research papers dealing with the photocatalytic degradation of CV dye using ZnO nanoparticles under UV irradiation [59,60]. In particular, it was evidenced that the complete CV decolorization was achieved for irradiation times generally higher than 80 min.…”
Section: Photocatalytic Activity Resultsmentioning
confidence: 59%
“…In particular, the organic impurities in contact with photocatalyst surface could act as radical scavengers, influencing the charge recombination process [57,58] and hence worsening the photocatalytic activity of ZnOac500 with respect to ZnOsas500 photocatalyst. It is worthwhile to note that the photocatalytic performances achieved with ZnOsas500 photocatalyst were better than those reported in some research papers dealing with the photocatalytic degradation of CV dye using ZnO nanoparticles under UV irradiation [59,60]. In particular, it was evidenced that the complete CV decolorization was achieved for irradiation times generally higher than 80 min.…”
Section: Photocatalytic Activity Resultsmentioning
confidence: 59%
“…At neutral pH conditions, Cheng et al (2004) found striking photo-aided dye pollution degradation over Fe (III)-loaded resin. According to Rao et al (1997), crystal violet was bleached photo catalytically in an aqueous solution of zinc oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the removal of CV dye from waste water is of great concern. [26] For the first time, photocatalytic degradation of CV over ZnO suspended in aqueous solution was carried out by Rao et al [27] After this work, different types of oxide semiconductors such as TiO 2 , [28] ZnO, [29] SnO 2 , [29] Co 3 O 4 , [30] α-Fe 2 O 3 , [31] In 2 O 3 , [32] BiVO 4 / FeVO 4 , [33] SnO 2 /BiOBr, [34] ZnO/AgBr, [35] rGO/TiO 2 /Co 3 O 4 , [36] and rGO/ZnO/TiO 2 [37] etc were developed and used for photocatalytic degradation of aqueous CV dye.…”
Section: Introductionmentioning
confidence: 99%